Room Temperature Self‐Healing Methyl Phenyl Silicone Rubbers Based on the Metal–Ligand Cross‐Link: Synthesis and Characterization. Issue 8 (20th February 2017) - Yu, Dajiang; Zhao, Xinxin; Zhou, Chuanjian; Zhang, Chen; Zhao, Shigui
Abstract : Copper ions are introduced into polysiloxanes with pendent Schiff‐base groups through metal–ligand coordination interaction. Coordination bonds which serve as cross‐linking points endow the silicone rubbers excellent self‐healing properties. Some samples can restore 87.0% strength after healing 1 h at 30 °C. The self‐healing mechanism is also studied by cross‐linking density analyzer. Abstract : Novel self‐healing silicone rubbers are prepared by a two‐step procedure: aminopropyl methyl phenyl polysiloxanes is first reacted with salicylaldehyde and then with copper acetate. The reversible nature of the metal–ligand coordination interaction between polysiloxanes with pendent Schiff‐base groups and Cu 2+ has endowed silicone rubbers with superior self‐healing properties. As compared with other self‐healing silicone rubbers based on hydrogen bonds or Diels–Alder reaction, this cross‐linked system shows high healing power. The materials are cut into two parts and put together in a mold for 1 h at 30 °C, observing a macroscopic healing and a strength recovery up to 87.0%.